Immigration Lawyers as Para-State Actors: Deportation of Non-Residents in Aotearoa New Zealand - Timothy P. Fadgen; Luke D. Oldfield (Societies)
This article considers the role of lawyers and immigration advisers in the deportation process for non-resident visa holders in New Zealand. In the process, this article adds to a small but growing literature on the role of immigration officials in the immigration policy space. We use Lipsky’s concept of the street-level bureaucrat and Lakhani’s notion of ‘para-state’ actors—those outside the formal apparatus of the state who nonetheless serve a central role in policy implementation—to advance our understanding of the deportation process. This qualitative study engaged in in-depth interviews with twenty-two (22) immigration lawyers and advisers to explore their experiences. We identify several themes about the importance of formal and informal networks for developing advocacy skills and tactics; how the features of the immigration system, lower levels of judicial scrutiny of decisions, and lower evidentiary requirements create spaces for lawyer advocacy and creativity; and how participants shared a commitment to social justice and camaraderie in their work that was essential to interactions with state officials and others. We contend that these efforts have the potential to reshape the state’s bordering practices yet are an often-overlooked area of study.